2001
DOI: 10.1007/pl00009998
|View full text |Cite
|
Sign up to set email alerts
|

Field microplot performance of the peach-almond hybrid GF-677 after inoculation with arbuscular mycorrhizal fungi in a replant soil infested with root-knot nematodes

Abstract: The effects of arbuscular mycorrhizae (AM) on the development and nutrition of the peach almond hybrid GF-677 rootstock in a replant soil heavily infested with Meloidogyne javanica were evaluated in field microplot conditions for two growing seasons. There was a significant beneficial effect of mycorrhizal inoculation on plant growth and nutrition in previously pasteurized replant soil. In natural replant soil, early inoculation with a mixed AM inoculum of Glomus intraradices, Glomus mosseae and Glomus etunica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

3
37
0
2

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(42 citation statements)
references
References 16 publications
(13 reference statements)
3
37
0
2
Order By: Relevance
“…Since AM fungi and RKN are all indigenous soil organisms and therefore co-exist in plant roots, the potential role of AM fungi as biocontrol agents and their protective effects on plants against RKN have been well documented Diedhiou et al 2003). Studies have shown that inoculation with AM fungi can significantly reduce RKN infestation and reproduction in some plant-nematode systems (Hol and Cook 2005) such as papaya with Meloidogyne incognita (Jaizme- Vega et al 2006), olive planting stocks with M. incognita and Meloidogyne javanica (Castillo et al 2006), tomato with M. incognita (Talavera et al 2001;Siddiqui and Akhtar 2007), pyrethrum with Meloidogyne hapla (Waceke et al 2001), Prunus rootstocks with M. javanica (Calvet et al 2001), and banana with M. javanica (Rodriguez and JaizmeVega 2005). In addition to enhancement of plant nutrition, especially P nutrition, establishment of arbuscular mycorrhizae may exert beneficial effects on plant growth though direct competition with RKN for infection sites and space, alteration of the composition of root exudates, or through activation of plant defense reactions and other mechanisms (Smith et al 1986;Azcón-Aguilar and Barea 1996;Harrier and Watson 2004;Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Since AM fungi and RKN are all indigenous soil organisms and therefore co-exist in plant roots, the potential role of AM fungi as biocontrol agents and their protective effects on plants against RKN have been well documented Diedhiou et al 2003). Studies have shown that inoculation with AM fungi can significantly reduce RKN infestation and reproduction in some plant-nematode systems (Hol and Cook 2005) such as papaya with Meloidogyne incognita (Jaizme- Vega et al 2006), olive planting stocks with M. incognita and Meloidogyne javanica (Castillo et al 2006), tomato with M. incognita (Talavera et al 2001;Siddiqui and Akhtar 2007), pyrethrum with Meloidogyne hapla (Waceke et al 2001), Prunus rootstocks with M. javanica (Calvet et al 2001), and banana with M. javanica (Rodriguez and JaizmeVega 2005). In addition to enhancement of plant nutrition, especially P nutrition, establishment of arbuscular mycorrhizae may exert beneficial effects on plant growth though direct competition with RKN for infection sites and space, alteration of the composition of root exudates, or through activation of plant defense reactions and other mechanisms (Smith et al 1986;Azcón-Aguilar and Barea 1996;Harrier and Watson 2004;Li et al 2006).…”
Section: Introductionmentioning
confidence: 99%
“…are economically important parasites of fruit plants. They induce the formation of giant cells and root galls that impair water and nutrient uptake to the shoots (Lordello, 1984), reducing the yield and fruit size, and causing the mineral deficiency that decreases plant longevity and a delay in the crop production (Calvet et al, 2001). Arbuscular mycorrhizal fungi and phytoparasitic root-knot nematodes are common soil and root inhabitants.…”
Section: Introductionmentioning
confidence: 99%
“…The interaction between AMF and nematodes results in improvement, reduction or has no effect on disease severity Maia et al, 2006). This interaction commonly occurs when the seedlings are transplanted to the field and both organisms are capable of colonizing the same roots (Calvet et al, 2001). The effect of the interaction AMF × plant nematodes depends on various factors such as nematode, fungus, and plant species, environmental conditions, time of mycorrhization and period of exposure to the nematode (Talavera et al, 2001).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Due to the beneficial effects of AMF on host plants under various biotic and abiotic conditions (Smith and Read, 1997), AMF are suggested to have the potential to serve as both biological fertilizers and biological control agents (Carling et al, 1996). Research has shown that AMF have interactions with root nematodes of many crop plant species including banana and Hyoscyamus niger (blacke henbane) with M. incognita (JaizmeVega et al, 1997;Pandey et al, 1999); Chrysanthemum with Meloidogyne hapla (Waceke et al, 2001); peanut with M. arenaria (Carling et al, 1996); Prunus rootstocks with M. javanica (Calvet et al, 2001); and olive planting stocks with Meloidogyne incognita and M. javanica (Castillo et al, 2006). In most circumstances, inoculation with AMF can increase the tolerance of host plants to nematodes.…”
Section: Introductionmentioning
confidence: 99%